2022
DOI: 10.1038/s42003-022-03600-9
|View full text |Cite
|
Sign up to set email alerts
|

Alignment between glioblastoma internal clock and environmental cues ameliorates survival in Drosophila

Abstract: Virtually every single living organism on Earth shows a circadian (i.e. “approximately a day”) internal rhythm that is coordinated with planet rotation (i.e. 24 hours). External cues synchronize the central clock of the organism. Consequences of biological rhythm disruptions have been extensively studied on cancer. Still, mechanisms underlying these alterations, and how they favor tumor development remain largely unknown. Here, we show that glioblastoma-induced neurodegeneration also causes circadian alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…A study on Drosophila has shown that re-adjustment of the light/dark cycles delayed GBM progression. 114 In rats with glioma, constant light conditions resulted in increased tumour volume, compared to the light/dark conditions. 98 Moreover, it is also known that eating can act as a zeitgeber and lead to circadian entrainment through an increase in the levels of plasma glucose and insulin.…”
Section: Perspectivesmentioning
confidence: 99%
“…A study on Drosophila has shown that re-adjustment of the light/dark cycles delayed GBM progression. 114 In rats with glioma, constant light conditions resulted in increased tumour volume, compared to the light/dark conditions. 98 Moreover, it is also known that eating can act as a zeitgeber and lead to circadian entrainment through an increase in the levels of plasma glucose and insulin.…”
Section: Perspectivesmentioning
confidence: 99%
“…Adult brain preparations were stained following the same protocol as in 50 . Dissections were always performed at ZT4-5 to avoid possible circadian-induced changes.…”
Section: -Immunolabeling Imaging and Image Analysismentioning
confidence: 99%

Socialization causes long-lasting behavioral changes

Gil-Martí,
Isidro-Mézcua,
Poza-Rodriguez
et al. 2024
Preprint
Self Cite
“…These two models have been widely used to identify new genes and signaling pathways involved in glioma progression. [41][42][43][44][45] Among the genes possibly involved in the progression of glioma, our recent data demonstrated the role of the serotonin 5-HT 7 receptor (5-HT 7 R) in a larval Drosophila model of glioma. 46 The human 5-HT 7 R expression in this animal model reduced larval lethality and partially restored dysregulated biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The second model, established by Chi et al 40 , allowed to induce glioma development specifically at the adult stage. These two models have been widely used to identify new genes and signaling pathways involved in glioma progression 41–45 …”
Section: Introductionmentioning
confidence: 99%